2015
DOI: 10.1007/s00234-015-1540-6
|View full text |Cite|
|
Sign up to set email alerts
|

MRI characterization of temporal lobe epilepsy using rapidly measurable spatial indices with hemisphere asymmetries and gender features

Abstract: Multiparametric MRI studies of hippocampus and amygdalae, including their hemispheric asymmetry, underscore better characterization of TLE. Rapidly measurable single-slice parameters (HA, PHA, MDR) can readily delineate TLE in a time-constrained clinical setting, which contrasts with customary three-dimensional hippocampal volumetry that requires many slice computation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…The inter-observer (radiologist vs. non-radiologist) variability (%) was non-significant (p>0.05, Student's unpaired t-test) for right and left hemispheric measurements of the data of healthy subjects (2.63±0.51 and 3.21±0.29 in men and 4.89±0.64 and 3.52±1.04 in women) by different observers for respective parameters. The inter-observer variability of the present study found to be consistent with our previous report (13).…”
Section: Status Of Brain Mri Parameterssupporting
confidence: 93%
See 4 more Smart Citations
“…The inter-observer (radiologist vs. non-radiologist) variability (%) was non-significant (p>0.05, Student's unpaired t-test) for right and left hemispheric measurements of the data of healthy subjects (2.63±0.51 and 3.21±0.29 in men and 4.89±0.64 and 3.52±1.04 in women) by different observers for respective parameters. The inter-observer variability of the present study found to be consistent with our previous report (13).…”
Section: Status Of Brain Mri Parameterssupporting
confidence: 93%
“…For AV measurement, "the segmentation of amygdala in coronal slices started from the level of uncinate gyrus, continued over the temporal horn of the lateral ventricle, and the amygdala was separated from hippocampus at its narrowest point. More anteriorly, the gray-white boundary was used to separate amygdala from substantia innominata, inferior putamen and claustrum" (13).…”
Section: Measurements Of Hv and Avmentioning
confidence: 99%
See 3 more Smart Citations